Pozycja powiatów wrocławskiego obszaru metropolitalnego na tle woj. dolnośląskiego - Zakrzewska-Półtorak, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper author discusses the stage and condition of Wroclaw metropolitan area. She compares positions of powiats of Wroclaw metropolitan area selected Lower Silesian powiats and whole voivodship. Among others, the following indicators are used: number of population, unemployment rate, average monthly gross wages and salaries, investment outlays, amount of national economy entities (without local entities) and net migration per 1000 population. Relations between big city - Wroclaw and other communes and powiats including Wroclaw metropolitan area are still too weak. Their development to high degree is determined by endogenous incentives without support of the capital of metropolitan area. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 160-166